Uma abordagem das máquinas térmicas no ensino da termodinâmica sob a ótica da aprendizagem significativa - Grasselli, Erasmo Carlos (2018)
This work aims to contextualize the content of thermodynamics through the construction of thermal machines and use them as a tool for presenting knowledge with the function of previous organizers for a later meaningful learning. The theoretical framework presents significant learning concepts based on learning theories covering studies by Piaget, Ausubel and specific contributions on the Teaching of the discipline Physics of Marco Antonio Moreira. The methodological approach is oriented to action-reflection-action research through the construction of three thermal machines (Stirling Motor, Steam Engine and Elastic Motor), with the purpose of offering a means to broaden the discussion about the importance of privileging learning contributing to the assimilation of the contents of thermodynamics to the Teaching of Physics in High School. During the research, an Educational Product was developed that was applied during the intervention with the students, serving as support for the development of classes related to the content addressed. The activities were programmed based on didactic sequences, which will be guided by the Potentially Significant Teaching Units (LIFOs). The results demonstrated an increase in the students 'interest in the content of the course, with the intensification of students' participation in the discussions and debates, evidenced by questions, opinions and arguments. The methodological diversification of the pedagogical practice and the punctual mediation of the teacher made the classes more attractive with the opportunity to interact at any moment with the practice of the construction of the thermal machines. The Educational Product facilitated the teaching process by stimulating research and research in the classes of the Physics discipline providing meaningful learning.